Lessons learned for animal health governance from bovine viral diarrhea eradication schemes in Scotland and Ireland - Shortall, Orla (Frontiers in Veterinary Science, 2022)
This paper explores lessons learned for animal health governance from bovine viral diarrhoea (BVD) eradication schemes in Scotland and Ireland, drawing on qualitative key stakeholder interviews. Bovine viral diarrhoea is an endemic cattle disease that causes animal health and welfare problems, as well as financial losses to farmers. Initial voluntary industry-led schemes to eradicate BVD were introduced in both countries in the 2010s, followed by compulsory phases involving legislation. The paper uses a theoretical framework of co-productive governance to analyse stakeholder views on how well the design and execution of the eradication schemes worked and what can be learned to inform future directions of animal health governance. The term ‘co-productive governance’ comes from the field of environmental governance and was developed to describe how science and politics influence each other in a context where governance is carried out by multiple actors working collaboratively (1). The results of key stakeholder interviews are analysed using the concepts of vision, context, knowledge and process. In relation to vision, the results show the importance of creating a clear narrative about the goal of disease eradication schemes. With regard to context, it is difficult to engage all actors in biosecurity governance, when initiatives are developed with the legacy of existing relationships and tensions. It is important to develop a clear scheme "narrative", which may incorporate or replace existing vet or farmer “narratives” about a disease. In relation to knowledge, the results showed the importance but political complexity of basing decisions on scientific research. One of the lessons learned was the benefit of involving industry stakeholders in setting scientific questions to inform the design of the scheme. And with reference to process, while interviewees were enthusiastic about future prospects for industry and government working together to achieve biosecurity goals co-productive governmance is not a panacea for enrolling all actors in biosecurity goals. The results also highlighted that farmers and other actors might object to an eradication scheme, whether it is run by government or private industry. Thus it is useful to keep questions about who benefits in what way from biosecurity governance open.